PENGARUH PENDIDIKAN AGAMA TERHADAP PERILAKU REMAJA DI DESA MULYA SUBUR KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN - Riantari, Indah; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research has intention to determine effect of religious education on the behavior of adolescent in mulya subur village pangkalan lesung distric pelalawan regency. Tenagee behavior is prayer and fasting, the behavior will be seen in three proportions namely the proportions of succes, the proportions of stimulus and the proportions of value. The theory used is a social axchange theory of George C. Humans. In this research the sample is some parents who have teenagers aged 12 – 21 years. The research design is descriptive quantitative with systematic random sampling approach. Data collection method is questionnaire, interviews and direct obsevasion. The analysis method is quatitative descriptive analysis presented in tables and then described in detail. From the result of the research conducted it is know that religious behavior in mulya subur village still enaogh. Religious education obtained by teenagers from parents and from TPA. Sometimes parents submit full child religious aducation to teacher at TPA, because of their look of understanding of religion. But with the teacher TPA can only provide education without being able to control the development of childrens nehavior at home. Keyword :Religious Education, Teenage Behavior.